Psychotherapy and counselling in practice : a narrative framework - Tantam, Digby (Cambridge, U.K. ; New York : Cambridge University Press, 2002)
This important and timely book gives a synthesis, based on actual cases, evidence, practice and experience, to describe the process of psychotherapy and identify the fundamental elements that lead to good outcome across all its varied schools. It is essential reading for anyone working with patients using a psychotherapy model.
Establishing the concerns -- Why start with the consideration of concerns? -- What is a concern? -- Concerns and psychotherapy -- The three elements of a concern -- The ternary model of psycho-analysis -- What is a concern? -- How does the discussion of concerns differ between medical or psychiatric practice, and the practice of psychotherapy? -- Assessment -- Causes and reasons -- Being a bit more practical about concerns -- What do these illustrations show about reasons and concerns? -- Preoccupying concerns -- Concerns about treatment -- Concerns about the therapeutic relationship -- The therapist's concerns -- Identifying concerns -- Evidence-based approach to concerns -- Whose concern is it anyway? -- Is the client always right? -- Concerns as we tell them to others -- Consensus or conflict between therapist and client? -- Clarifying the focus -- What is psychotherapy after all? -- Values -- My values are me -- 'Helping' -- Truthfulness, honesty and effectiveness -- Authority and pathology -- Ethics -- Congruence of values -- The client's treatment values -- What life means. Emotional flavour -- Why give emotions such importance? What about relationships? -- Shame and disgust -- Emotions as a guide -- How to act when plans fail -- Maintaining the social bond -- Making decisions, particularly ethical decisions -- Who am I? -- I in the interpersonal domain -- Emotional meaning -- Projection and emotional meaning -- Strong emotional meanings -- Strong emotors and the fear of extinction -- Emotional meaning and choice.
Includes bibliographical references (297-311) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Psychotherapy; Psychotherapy -- methods; Counseling -- methods; Psychotherapy; Psychothérapie.; PSYCHOLOGY -- Psychotherapy -- General; Psychotherapy; Psychotherapie; Counseling; Verteltheorie